Land-Use Planning and the Right to Compensation in the Netherlands - Fred Hobma; Willem Wijting (Washington University Global Studies Law Review, 2007)
This Article primarily discusses governmental liability in the Netherlands for the consequences of land planning decisions made in the public interest.
Keywords: Regulatory takings; Just compensation (Eminent domain); Compensation (Law); Land use planning; Property rights; Netherlands